Environmental Crime as a Threat to Ecological Security in Poland - Piątkowska, Bożenna (PRAWO i WIĘŹ, 2024)
The paper discusses various threats that are an integral part of the daily lives of humans and all other living organisms worldwide. Despite numerous attempts and regulations introduced to protect the environment and ensure safety, achieving stability in this area remains elusive. The natural environment is continuously exposed to various threats, just as ecological security is at risk. In a synthetic approach, the author addresses these issues and attempts to answer the question: how does environmental crime affect the ecological security of Poland? Unfortunately, this type of crime has a very negative impact on ecological security, which is not encouraging. From the analysis of available literature and statistical data, the following conclusion can be drawn. To effectively combat environmental crime in Poland, actions should be taken to strengthen law enforcement, increase the powers of law enforcement agencies, promote cross-sectoral cooperation, and raise public awareness about environmental protection. Additionally, it is necessary to enhance international cooperation to combat transboundary environmental crime.